Komunikasi Persuasif Cuantomonologi Dalam Meningkatkan Pengetahuan Masyarakat Terhadap Cryptocurrency Di Kabupaten Karawang - Muhammad Ramdhan Sampurna; Firdaus Yuni Dharta; Dadan Kurniansyah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to examine and analyze cuantomonology persuasive communication in increasing public knowledge of cryptocurrency in Karawang Regency. The theory used is affective-cognitive consistency theory in persuasive communication Suryanto (2017) in which there are four variable dimensions namely or source credibility, environmental influence, message and message continuity. The method used in this research is descriptive qualitative. The data collection technique was carried out by triangulation, then the data were analyzed through three stages which included reduction, presentation and conclusion. The results of the research and discussion show that people who still have views of illegal trading with Cryptocurrency are the same thing as well as the lack of expertise of Cuantomonology communicators in building persuasiveness to the community. The time that is often used by Cuantomonology to persuade the public is when the price of crypto coins rises or there is a company that provides a special price when buying with crypto coins, with the contents of the message in the form of educating the importance of cryptocurrency. Messages are delivered directly and simply. Cuantomonology is unable to optimize the presence of new media in distributing Cryptocurrency information to the people of Karawang